Comparing the Pharmacokinetics of Doxylamine/Pyridoxine Delayed‐Release Combination in Nonpregnant Women of Reproductive Age and Women in the First Trimester of Pregnancy. (24th January 2013) - Matok, Ilan; Clark, Shannon; Caritis, Steve; Miodovnik, Menachem; Umans, Jason; Hankins, Gary; Koren, Gideon
Abstract Although Diclectin (doxylamine/pyridoxine delayed‐released combination) is widely used in Canada, its pharmacokinetics (PK) during pregnancy has never been described. The objective of this study was to compare the PK of doxylamine/pyridoxine delayed‐released combination in pregnant versus nonpregnant women. The apparent clearances (CL) of doxylamine and pyridoxal 5′‐phosphate (PLP; the active metabolite of vitamin B6) during the first‐trimester pregnancy in women who participated in a Diclectin randomized trial were compared with those of healthy, adult, nonpregnant women who participated in a voluntary PK trial. Eighteen nonpregnant women were compared with 50 pregnant women who were treated with Diclectin. There was no difference in the apparent CL of doxylamine in women in their first trimester of pregnancy when compared with nonpregnant women on day 4 (median = 196.7 vs 249.5 mL/h/kg, respectively, P = .065), day 8 (median = 248.4 vs 249.5 mL/h/kg, respectively, P = .82), and day 15 (median = 200.9 vs 249.5 mL/h/kg, respectively, P = .55). No difference was found in the apparent CL of PLP on day 15 (median = 342.3 vs 314.7 mL/h/kg, respectively, P = .92). There was no pregnancy‐induced effect in the apparent CL of either doxylamine or PLP in women during the first trimester of pregnancy despite the existence of morning sickness.